Influence of structural parameters of friction pair on oil temperature rise in hydro-viscous clutch. Issue 1 (26th September 2019) - Li, Zhibao; Xie, Fangwei; Sun, Junyu; Zhu, Jie; Zheng, Xudong; Guo, Xinjian; Wang, Yun; Hua, Yinqun
Abstract : Purpose: The purpose of this paper is to study the temperature characteristics of hydro-viscous clutch with different structure of friction disks and obtain the distribution of film temperature. Design/methodology/approach: The mathematical model of oil film between friction disks with radial grooves is established. Based on the flow rate equation, the temperature rise equation of oil film is deduced. Considering two-phase flow, the temperature distribution in the oil shear stage and the effects of the ratio of inner radius to outer radius on film temperature rise is studied by using computational fluid dynamics (CFD) technology. Findings: The results show that when input speed is constant, the increase in the ratio of inner to outer radius leads to an increase in the peak temperature and the decrease in the ratio results in a larger increasing rate of temperature. Originality/value: These results are of interest for the study of hydro-viscous drive and its applications. This study can also provide a theoretical basis for the mechanism of temperature rise by considering the effect of two-phase flow.